Effect of Low‐Magnitude Mechanical Stimuli on Bone Density and Structure in Pediatric Crohn's Disease: A Randomized Placebo‐Controlled Trial. (31st March 2016) - Leonard, Mary B; Shults, Justine; Long, Jin; Baldassano, Robert N; Brown, J Keenan; Hommel, Kevin; Zemel, Babette S; Mahboubi, Soroosh; Howard Whitehead, Krista; Herskovitz, Rita; Lee, Dale; Rausch, Joseph; et al.
ABSTRACT: Pediatric Crohn's Disease (CD) is associated with low trabecular bone mineral density (BMD), cortical area, and muscle mass. Low‐magnitude mechanical stimulation (LMMS) may be anabolic. We conducted a 12‐month randomized double‐blind placebo‐controlled trial of 10 minutes daily exposure to LMMS (30 Hz frequency, 0.3 g peak‐to‐peak acceleration). The primary outcomes were tibia trabecular BMD and cortical area by peripheral quantitative CT (pQCT) and vertebral trabecular BMD by QCT; additional outcomes included dual‐energy X‐ray absorptiometry (DXA) whole body, hip and spine BMD, and leg lean mass. Results were expressed as sex‐specific Z ‐scores relative to age. CD participants, ages 8 to 21 years with tibia trabecular BMD <25th percentile for age, were eligible and received daily cholecalciferol (800 IU) and calcium (1000 mg). In total, 138 enrolled (48% male), and 121 (61 active, 60 placebo) completed the 12‐month trial. Median adherence measured with an electronic monitor was 79% and did not differ between arms. By intention‐to‐treat analysis, LMMS had no significant effect on pQCT or DXA outcomes. The mean change in spine QCT trabecular BMD Z ‐score was +0.22 in the active arm and –0.02 in the placebo arm (difference in change 0.24 [95% CI 0.04, 0.44]; p  = 0.02). Among those with >50% adherence, the effect was 0.38 (95% CI 0.17, 0.58, p < 0.0005). Within the active arm, each 10% greater adherence was associated with a 0.06 (95% CI 0.01, 1.17, p  = 0.03) greater increase in spine QCT BMD Z ‐score. Treatment response did not vary according to baseline body mass index (BMI) Z ‐score, pubertal status, CD severity, or concurrent glucocorticoid or biologic medications. In all participants combined, height, pQCT trabecular BMD, and cortical area and DXA outcomes improved significantly. In conclusion, LMMS was associated with increases in vertebral trabecular BMD by QCT; however, no effects were observed at DXA or pQCT sites. © 2016 American Society for Bone and Mineral Research.